Wolfville - Lewis, Alfred Henry, 1857-1914; Remington, Frederic, 1861-1909 (New York : Frederick A. Stokes Company, 1897)
The Old Cattleman has many tales to tell of the days when the Wild West was truly wild, having spent his entire life in Wolfville--a time when desperadoes and mule-skinners, outlaws and lawmen, runaways and rawhiders, ran the town.
Wolfville's first funeral -- The Stinging Lizard -- The story of Wilkins -- The washwoman's war -- Enright's pard, Jim Willis -- Tucson Jennie's heart -- Tucson Jennie's jealousy -- The man from Red Dog -- Cherokee Hall -- Texas Thompson's election -- A Wolfville foundling -- The man from Yellowhouse -- Jacks up on eights -- The rival dance-halls -- Slim Jim's sister -- Jaybird Bob's joke -- Boggs's experience -- Dawson & Rudd, partners -- Mace Bowman, sheriff -- A Wolfville Thanksgiving -- Bill Hoskins's coon -- Old Sam Enright's romance -- Piñon Bill's bluff -- Crawfish Jim.
Short stories.
BAL
McCracken, H. Remington, artist
Keywords: Western stories; Western stories